Preface - Grazyna Demenko (Archives of Acoustics, 2014)
The Polish Phonetic Association have the great pleasure to give the "Archives of Acoustic" Readers possibility acquaint with topics presented at the conference Applications of Phonetic Research to Speech Analysis, Synthesis and Recognition, which was held in 2005 in Kraków, and the conference Speech Signal Annotation, Processing and Synthesis organised by Department of Phonetics Adam Mickiewicz University in Pozna´n, and Institut für Kommunikationswissenschaften in Bonn, and supported by Alexander von Humboldt Stiftung under auspices: The International Speech Communication Association ISCA and Polish Phonetic Association.